Wood growth patterns of Macrolobium acaciifolium (Benth.) Benth. (Fabaceae) in Amazonian black-water and white-water floodplain forests - Schöngart, Jochen; Piedade, Maria Teresa Fernandez; Wittmann, Florian Karl; Junk, Wolfgang Johannes; Worbes, Martin (Oecologia, 2005)
Macrolobium acaciifolium (Benth.) Benth. (Fabaceae) is a dominant legume tree species occurring at low elevations of nutrient-poor black-water (igapó) and nutrient-rich white-water floodplain forests (várzea) of Amazonia. As a consequence of the annual long-term flooding this species forms distinct annual tree rings allowing dendrochronological analyses. From both floodplain types in Central Amazonia we sampled cores from 20 large canopy trees growing at identical elevations with a flood-height up to 7 m. We determined tree age, wood density (WD) and mean radial increment (MRI) and synchronized ring-width patterns of single trees to construct tree-ring chronologies for every study site. Maximum tree age found in the igapó was more than 500 years, contrary to the várzea with ages not older than 200 years. MRI and WD were significantly lower in the igapó (MRI=1.52±0.38 mm year-1, WD=0.39±0.05 g cm -3) than in the várzea (MRI=2.66±0.67 mm year -1, WD=0.45±0.03 g cm-3). In both floodplain forests we developed tree-ring chronologies comprising the period 1857-2003 (n=7 trees) in the várzea and 1606-2003 (n=13 trees) in the igapó. The ring-width in both floodplain forests was significantly correlated with the length of the terrestrial phase (vegetation period) derived from the daily recorded water level in the port of Manaus since 1903. In both chronologies we found increased wood growth during El Niño events causing negative precipitation anomalies and a lower water discharge in Amazonian rivers, which leads to an extension of the terrestrial phase. The climate signal of La Niña was not evident in the dendroclimatic proxies. © Springer-Verlag 2005.
Keywords: Dendrochronology; Floodplain Forest; Growth; Legume; Wood; Age; Climate; Comparative Study; Growth, Development And Aging; Histology; Legume; Plant Stem; River; Tree; Age Factors; Climate; Fabaceae; Plant Stems; Rivers; Trees; Amazonia; South America; Western Hemisphere; World; Fabaceae; Macrolobium Acaciifolium